Właściwości reologiczne żeli WPI otrzymanych przez bezpośredni dodatek soli - Paweł Glibowski; Stanisław Mleko; Waldemar Gustaw; Ewa Chełstowska (Agronomy Science, 2004)
The effect of protein and sodium chloride was studied by analyzing the rheological and textural properties of the gel. The one-stage and two-stage heating process was used. The first step was carried out at pH 8. Disulfide bonds connected the protein molecules. In the second step carried out at pH 7 noncovalent bonds were formed. Increasing NaCl and protein concentration increased gel strength. Two-stage heating process increased gel strength at lower protein concentrations (6%) regardless of NaCl concentration. The gel was harder at low sodium chloride concentration (up to 150 mmol) regardless of protein concentration.